NEMATODE PARASITES OF THE NEOTROPICAL RATTLESNAKE, CROTALUS DURISSUS LINNAEUS, 1758 (OPHIDIA, VIPERIDAE) FROM BRAZIL: NEW RECORDS AND GENERAL ASPECTS - Magalhães Pinto, Roberto (2010)
Forty-six samples of nematodes recovered from Brazilian specimens of Crotalus durissus Linnaeus, 1758, commonly named rattlesnake were studied. Snakes either died in captivity, under which they were kept for production of serum, or were found dead in nature. Other samples of nematodes from this host and preserved} in the Helminthological Collection of the Oswaldo Cruz Institute (CHIOC) were also analyzed. The most prevalent species were those of the genus Ophidascaris Baylis, 1920: O. arndti Sprehn, 1929, O. durissus Panizzutti, Santos, Vicente, Muniz-Pereira & Pinto, 2003, O. sicki Freitas, 1951, O. tuberculatum Siqueira, Panizzutti, Muniz-Pereira & Pinto, 2005 and Ophidascaris sp., followed by specimens allocated in Hexametra Travassos, 1920: H. boddaertii (Baird, 1860) Kreis, 1944, and Kalicephalus Molin, 1861: K. inermis macrovulvus Caballero, 1954, Kalicephalus sp. Also, specimens representing the genera Hastospiculum Skrjabin, 1923: Hastospiculum sp., Physaloptera Rud, 1819: Physaloptera sp. and Travassosascaris Sprent, 1978: T. araujoi (Schneider, 1866) Sprent, 1978 were identified, as well. The species Ophidascaris arndti, O. sick, O. tuberculatum, K. inermis macrovulvus and Physalopera sp., represent new occurrences in this host. Species are briefly presented and figured, with emphasis in the cross sections of buccal structures.